2015
DOI: 10.1139/cjz-2014-0119
|View full text |Cite
|
Sign up to set email alerts
|

Age, but not sex and seasonality, influence Haemosporida prevalence in White-banded Tanagers (Neothraupis fasciata) from central Brazil

Abstract: Despite many studies on avian blood parasites, we still have a limited understanding of the mechanisms that drive patterns of Haemosporida infection among tropical birds, including effects associated with sex, age, and seasonality. Using molecular and morphological methods for blood parasite detection, we found that juvenile White-banded Tanager (Neothraupis fasciata (Lichtenstein, 1823)) had lower haemosporidian prevalence than adults in a population within Central Brazil. However, no sex or seasonal differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 43 publications
(75 reference statements)
3
20
0
Order By: Relevance
“…For example, in our study, most birds were sampled during reproductive season which is related to the relapse stage of chronic haemosporidian parasite infection (Valkiūnas, 2005; Asghar et al, 2011). Additionally and according to other studies (McCurdy et al, 1998; Fecchio et al, 2015), no sex-biased haemosporidian prevalence was observed in the Thorn-tailed Rayadito, this could be in concordance with the similar reproductive costs and exposure to vectors for monogamous species in both mates (McCurdy et al, 1998; Fecchio et al, 2015).…”
Section: Discussionsupporting
confidence: 88%
“…For example, in our study, most birds were sampled during reproductive season which is related to the relapse stage of chronic haemosporidian parasite infection (Valkiūnas, 2005; Asghar et al, 2011). Additionally and according to other studies (McCurdy et al, 1998; Fecchio et al, 2015), no sex-biased haemosporidian prevalence was observed in the Thorn-tailed Rayadito, this could be in concordance with the similar reproductive costs and exposure to vectors for monogamous species in both mates (McCurdy et al, 1998; Fecchio et al, 2015).…”
Section: Discussionsupporting
confidence: 88%
“…Zuk and McKean, 1996; Deviche et al 2010) and others none (e.g. Ricklefs et al 2005; Latta and Ricklefs, 2010; Fecchio et al 2015; Granthon and Williams, 2017). Similar to the latter studies, neither age (AHY or HY) nor sex had significant effects on parasite infection intensity in red crossbills in this study, which may be due to more or less equal distribution of infection intensities among birds exhibiting symptoms of Haemoproteus infection (Norte et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Patterns of parasitism might even be non‐linear, reflecting both accumulation of infective stages and age‐related strength of immune responses to mounting infections (Woolhouse , Sorci ). Age biases in parasitism do occur across host taxa, and among avian hosts both juvenile (Isomursu et al ) and adult (Fecchio et al ) age biases in parasitism have been observed, though, as mentioned above, the pattern may be embedded in an interaction between host age and host sex (Isomursu et al , Durkin et al ).…”
Section: Introductionmentioning
confidence: 99%